Assessment of information needs of home caregivers - Maria José Lumini Landeiro; Heloísa Helena Ciqueto Peres; Teresa Martins (Universidade Federal de Santa Maria, 2015)
Aim: to identify needs, difficulties, essential information and suitability of the use of educational technologies of family caregivers in providing informal care to dependent person in the household. Method: descriptive exploratory study with an intentional sample of caregivers and data collection performed by semi-structured interviews to 12 caregivers using sociodemographic questionnaire and assessment by Barthel Index. Results: participants were mostly women, daughters, in professional activity and mostly 57 years-old. Dependent people were mostly women, most of the sample was totally dependent and mostly 78 years-old. It was identified a need for information in order to develop skills in knowledge, instrumental and social support for the self-care on feeding, mobility and locomotion and the usefulness of educational technology. Conclusion: this study contributes to a better performance of nurses in training of caregivers on the care of the dependent person